International spillovers from US monetary policy: evidence from Asian bank-level data - Lee, S; Bowdler, C (Elsevier, 2022)
We investigate spillovers from US monetary policy to bank lending in Asia. When Asian banks use funding denominated in US dollars and other currencies, a tightening of US monetary policy will contract bank loan supply via funding volumes/costs. Panel regressions demonstrate such effects on bank lending volumes and prices in Asia, holding constant local economic conditions. Supplementary results are not inconsistent with transmission channels via funding availability and funding costs. Our results extend work on the impact of US monetary policy on international inter-bank funding flows and are consistent with several of the implications from findings in that literature.